Comparison of the efficacies of entecavir 0.5 and 1.0 mg combined with adefovir in patients with chronic hepatitis B who had failed on prior nucleos(t)ide analogue treatments. Issue 6 (24th February 2015) - Cho, Yuri; Lee, Jeong‐Hoon; Yu, Su Jong; Yoon, Jung‐Hwan; Lee, Hyo‐Suk; Kim, Yoon Jun
<x xml:space="preserve">Abstract</x> Entecavir (ETV) plus adefovir (ADV) combination therapy is one of the useful treatment option for the patients with chronic hepatitis B (CHB) who had failed on prior nucleos(t) ide analogue (NA) treatments. This study compared the efficacies of the combinations of ETV 0.5 mg plus ADV and ETV 1.0 mg plus ADV in patients who had failed on prior multiple NA treatments. This retrospective analysis included 148 consecutive patients with CHB infection in Korea (n = 37 with ETV 0.5 mg plus ADV and n = 111 with ETV 1.0 mg plus ADV). The virological and biochemical responses were compared between the two groups. The cumulative probability of viral suppression of ETV 0.5 mg plus ADV was not inferior to that of ETV 1.0 mg plus ADV (hazard ratio [HR], 0.64; 95% confidence interval [CI], 0.38–1.08; P = 0.094). The changes in serum HBV DNA level in the ETV 0.5 mg plus ADV group were not different between the two groups over 12 months. Moreover, no significant difference was observed in acquiring ETV‐resistant variants between the two groups during the treatment (HR, 0.95; P = 0.953). This study suggests the proof‐of‐concept that the lower dose of NA in combination with other NA might be the theoretical option for rescue combination therapy in patients with CHB who had failed on prior multiple NA treatments in order to reduce systemic exposure and possible side effects of NA. J. Med. Virol. 87:999–1007, 2015. © 2015 Wiley Periodicals, Inc.